Forest respiration from eddy covariance and chamber measurements under high turbulence and a bark beetle epidemic - Speckman, Heather, author; Ryan, Michael G., advisor; Parton, William J., advisor; Ham, Jay M., committee member; Denning, A. Scott, committee member (Colorado State University. Libraries, 2013)
Eddy covariance (EC) enables continuous estimates of carbon, water, and energy fluxes, and a global network of >500 sites (www.fluxnet.ornl.gov) has resulted in major advances in understanding ecosystem-scale biogeochemical cycling. However, long-term sums of net ecosystem exchange, photosynthesis and respiration fluxes have uncertainties because of potential measurement biases in respiration fluxes at night. Many studies have demonstrated that EC estimations of flux during the night are lower than chamber measurements--with low turbulence at night potentially causing the difference. A bark beetle outbreak at the GLEES Ameriflux site provided a unique opportunity to compare chamber and EC estimates of ecosystem respiration (R) under conditions of high turbulence (summer night mean u* = 0.7 m s-1) and 85% mortality of the aboveground respiring biomass due to a bark beetle epidemic. Chamber-based estimates of R were developed from periodic foliage, wood and soil CO2 efflux measurements fit to models of phenological seasonal change and diurnal temperature response. These models estimated ecosystem mean nightly respiration to have declined 32% after the bark beetle epidemic (7.0 ±0.22 μmol m-2 s-1 in 2005 to 4.8 ±0.16 μmol m-2 s-1 in 2011). The decrease was entirely due to the loss of aboveground respiration, soil efflux remained constant throughout the epidemic. Unlike chamber estimates, nighttime EC measurements did not decline after 85% of the forest basal area had been infested or killed by bark beetles, mean nighttime NEE of 3.0 μmol m-2 s-1 for 2005 and 2011. These EC values were significantly lower than chamber estimates of respiration for the same time periods (58% lower in 2005, and 34% in 2011). Despite the large difference in values, the two estimates of R were correlated (yearly r2 ranging from 0.18-0.60). This study suggests that the traditional discrepancy of nighttime EC and chamber estimates of ecosystem respiration are not caused by insufficient turbulence (results proved robust to extreme u* filter > 0.7 m s-1). Other sources of error are investigated for both techniques. To further explore this discrepancy, we suggest the installation of a second EC system below the canopy to improve understanding of air flows and fluxes throughout the ecosystem. This discrepancy must be resolved before scientific confidence can be attained in the true value of ecosystem carbon flux.
Keywords: bark beetles; chamber; ecosystem respiration; eddy covariance; turbulence; u* filtering